POPULATION DYNAMICS OF INDIAN MACKEREL BASED ON DATA PROM MANGALORE DURING 1967-1975 - Yohannan, T M (Indian Journal of Fisheries, 2011)
The total mortality rate (Z), as on data collected at Mangalore during 1967-75, ranged between 2.54 and 6.21. Since the total mortality had no regression on Ashing intensity the natural mortality rate (M) was calculated as 1.5 from the effective life span of mackerel. K,t„ and WQ, values were estimated based on the growth in weight. The studies indicated that mackerel can withstand heavy fishing mortalities (F) and the value of F that gives the maximum yield is 6.00. The recommended age at entry into the exploited phase ( t . ) is 8 months instead of the present 6 months. Increasing the F value to 6.00 and tp. to 8 months it is found that the existing quantity of the average standing stock can give an average annual catch of 1,98,870 tonnes instead of the present 96,451 tonnes.